Remaja Mengenali Serangan Jantung Koroner - Apriyatmoko, Raharjo; Aini, Faridah (UNIVERSITAS NGUDI WALUYO, 2020)
The involvement of all components in society including adolescents is important to reduce the high number of deaths due to heart attacks. But various health programs in school have not touched on the topic. Through community service with a participatory approach-based health education is expected to improve adolescents' ability to handle heart attacks. The participatory approach involves fully the role of all related components in planning, implementing and evaluating the program. Program procedures include preparation stage, participant recruitment, training, and evaluation monitoring. The recruitment results included 56 students who were active in Youth Red Cross activities. Preliminary measurement shows 87.86% of students have less knowledge and ability in coronary heart disease. An increase in significantly was shown after the program was run, where there was a 70% increase in good categorie. The method used can be said to be effective in improving adolescent abilities. There needs to be ongoing action on the program in particular improving young men's involvement and strengthening students' motivation to share their knowledge and hone skills through ongoing coaching programs.AbstrakKeterlibatan semua komponen di masyarakat termasuk remaja penting untuk mengurangi tingginya kematian akibat serangan jantung. Namun berbagai program kesehatan pada anak sekolah belum menyentuh topik tersebut. Melalui pengabdian masyarakat dengan pendidikan kesehatan berbasis pendekatan partisipatif diharapkan dapat meningkatkan kemampuan remaja dalam penanganan serangan jantung. Pendekatan partisipatif melibatkan secara penuh peran semua komponen terkait dalam merencanakan, melaksanakan dan mengevaluasi program. Prosedur program yang dijalankan meliputi tahap persiapan, perekrutan peserta, pelatihan, serta monitoring evaluasi. Hasil perekrutan mendapatkan peserta sejumlah 56 siswa yang aktif dalam kegiatan Palang Merah Remaja. Pengukuran awal menunjukkan 87,86% siswa memiliki pengetahuan dan kemampuan yang kurang dalam penyakit jantung koroner. Peningkatan siknifikan ditunjukkan setelah program dijalankan, dimana terjadi peningkatan pada katagori baik sebesar 70%. Metode yang digunakan dapat dikatakan efektif dalam peningkatan kemampuan remaja. Perlu ada tindakan berkelanjutan pada program khususnya peningkatan keterlibatan remaja pria dan penguatan motivasi siswa untuk menyebarkan pengetahuan yang dimiliki dan mengasah ketrampilan melalui program pembinaan berkelanjutan.